Development of an Accounting E-Module with Book Creator to Improve Student Learning Achievement in Accounting Material as an Information System for Regina Pacis Bajawa High School Students - Mariani Ketut Sary (International Journal of Studies in International Education, 2024)
The objectives of this research are: (1) To produce an e-module accounting module to improve the learning achievement of SMAS Regina Pacis Bajawa students. (2) Examining the feasibility of accounting e-modules to improve the learning achievement of SMAS Regina Pacis Bajawa students. (3) Examining the effectiveness of the accounting e-module in improving the learning achievement of SMAS Regina Pacis Bajawa students.This type of research is research and development research with the ADDIE model. With an experimental trial design using a pre-test – post-test model. The test subjects in this research were class XI IPS D SMAS Rergina Pacis Bajawa. Product suitability is tested by media experts, material experts, learning practitioners, namely teachers, and media users, namely students. Data collection was carried out using observation, interviews, questionnaires and tests. The data collection instruments used were interview guides, expert validation questionnaires, teacher response questionnaires, student response questionnaires, and accounting questions as an information system. Development products are assessed based on the appropriateness of media design and learning materials. The feasibility of the resulting learning media was analyzed using a conversion of 4 eligibility criteria, namely very good, good, poor and very poor.Results of the research (1) An accounting e-module with a book creator has been developed to improve student learning achievement. (2) The accounting e-module with book creator was assessed in the very appropriate category by media experts with a score of 91.66%, a score of 84.61% in the very appropriate category from material experts, a score of 100% in the very appropriate category from teachers and a score of 87 .14% in the very feasible category was obtained from student assessments. (3) E-module accounting module with book creator can improve the learning achievement of Regina Pacis Bajawa High School students. It can be seen that there is an increase in the average student score from the pretest of 57.18 to 85.78 in the posttest.